Kurdish Identity Between Modernism and Tradition - Ahmadifar, Asst.Prof. Dr. Rashid (Sulaimani Journal for Humanities, 2025)
Over the past century, Kurdistan has undergone profound transformations as part of the modern history of the Middle East, reshaping the life-world of its inhabitants, particularly in Iranian Kurdistan. This study examines the tension between traditional values upheld by older generations and modern influences adopted by youth. Understanding this interplay is crucial for grasping the socio-cultural evolution in this unique context. Method: Using a qualitative approach grounded in grounded theory, data were collected via in-depth interviews, oral histories, and participatory observations in Mukerian. The analysis draws on Engelhart’s value evolution and Giddens’ reflexive modernity. This approach allows for a nuanced understanding of how modernization interacts with traditional values in this region. Discussion: This study highlights a spectrum of objective and subjective changes occurring in the Kurdish life-world, shaped by the distinct historical, political, and cultural context of Mukerian. Key areas of transformation include religious and spiritual values, social interactions, family dynamics, economic, lifestyles, and artistic expressions encompassing clothing, music, art, and literature. So, the study reveals a dialectic of de-traditionalization and traditionalization. While elders preserve traditions in religion and family, youth embrace secular education and urban consumerism. This duality reflects the broader tensions experienced by communities navigating the challenges of modernization while striving to maintain their cultural heritage. Findings: The findings highlight the importance of recognizing the fluidity of identity, the role of cultural preservation, and the ongoing negotiation of values in a rapidly changing world. Through this lens, it becomes clear that Kurdish identity is not merely a relic of the past but a vibrant, evolving narrative that continues to shape the lives of individuals and communities. This duality in this research is conceptualized as pseudo-modernism with Kurdish exclusivity, reflecting globalization’s local negotiation.
Keywords: Kurdish identity; Modernization; Grounded theory; Life world; Pseudomodernism; Mukerian